Professional perspectives on service user and carer involvement in mental health care planning: A qualitative study. Issue 12 (December 2015) - Bee, Penny; Brooks, Helen; Fraser, Claire; Lovell, Karina
Abstract: Background: Involving users/carers in mental health care-planning is central to international policy initiatives yet users frequently report feeling excluded from the care planning process. Rigorous explorations of mental health professionals' experiences of care planning are lacking, limiting our understanding of this important translational gap. Objectives: To explore professional perceptions of delivering collaborative mental health care-planning and involving service users and carers in their care. Design: Qualitative interviews and focus groups with data combined and subjected to framework analysis. Setting: UK secondary care mental health services. Participants: 51 multi-disciplinary professionals involved in care planning and recruited via study advertisements. Results: Emergent themes identified care-planning as a meaningful platform for user/carer involvement but revealed philosophical tensions between user involvement and professional accountability. Professionals emphasised their individual, relational skills as a core facilitator of involvement, highlighting some important deficiencies in conventional staff training programmes. Conclusions: Although internationally accepted on philosophical grounds, user-involved care-planning is poorly defined and lacks effective implementation support. Its full realisation demands greater recognition of both the historical and contemporary contexts in which statutory mental healthcare occurs.